Rescrewing the embolized duct occluder using the delivery cable - Nageswara Rao Koneti (Annals of Pediatric Cardiology, 2014)
We report the successful re-screwing of the embolized duct occluder (DO) in three children for retrieval and to attempt redeployment. The DO was embolized into descending aorta immediately after the deployment in one child and within 24 h after the procedure in two further patients. The DO was re-screwed back by the DO delivery cable, using "sheath in sheath" in all three cases; however, successful retrieval could be done only in two. Repositioning in the patent ductus arteriosus (PDA) was done using the same device in those two children and surgical removal was needed in third child with perimembranous ventricular septal defect.